An economic heory of depression and its impact on health behavior and longevity - Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
In this paper, I introduce depression to the economics of human health and aging. Based on studies from happiness research, depression is conceptualized as a drastic loss of utility and value of life (life satisfaction) for unchanged fundamentals. The model is used to explain how untreated depression leads to unhealthy behavior and adverse health outcomes: depressed individuals are predicted to save less, invest less in their health, consume more unhealthy goods, and exercise less. As a result, they age faster and die earlier than non-depressed individuals. I calibrate the model for an average American and discus the socioeconomic gradient of health and depression as well as the hump-shaped association of antidepressant use with age. Delays in treatment for depression in young adulthood are predicted to have significant repercussions on late-life health outcomes and longevity.
Keywords: D15; D91; I10; I12; 330; depression; depression therapy; health behavior; aging; longevity